Teaching journalism prior to and after the demise of Christian higher education at Potchefstroom - Froneman, J. D. (Koers, 2009)
This article explores how the step-by-step changes to the Potchefstroom University for Christian Higher Education (resulting in the merger with the University of the North-West to form the North-West University [NWU]) impacted on the teaching of journalism at the Potchefstroom Campus. It was particularly relevant in 2009, as 50 years of teaching journalism and other communication subjects were celebrated by the School of Communication Studies on the Potchefstroom Cam-pus of the NWU. The article thus also has a definite historio-graphical intention – more specifically as an attempt at writing micro-historiography. It aims to illustrate how a definite Christian perspective on journalism was substituted for a slimmer “value-driven” approach sans an explisit religious dimension. Although it has been suggested by the vice-chancellor that lecturers had the right to express their views in class (including views based on Christian principles), it is argued here that the termination of the formal Christian approach made it very difficult, if not impossible, for lecturers to continue as in the past. As a result of the value-driven approach professional and institutional ethical codes are now used as a basic point of departure. This, however, does not satisfy those who prefer a more fundamental Christian approach to journalism. It is suggested that if this reading of the situation was erroneous, perhaps those Christians with a more positive view of the “name change” could give clearer leadership on how Christian perspectives on science (and journalism) can realistically be accommodated in the curriculum.